NITRITE DETERMINATION BY THE DIFFERENTIAL PULSE POLAROGRAPHIC METHOD - Karaoglan, Gulnur Keser (YILDIZ TECHNICAL UNIV, 2005)
In this work; the optimum conditions of the differential pulse polarographic method conditions of the polarographic reduction of diphenylnitrosoamine which was occured by nitrite ion and diphenylamine in perchloric acidic medium and thiocyanate ion as catalyst, were determined. At these polarogram conditions, nitrite ion gave a maximum diffusion current at -0.56 V. The differential pulse polarograms were obtained by working at these conditions with 1 mL portions of the solutions containing 0.5-2.5 mu g/mL nitrite ion (n=5). A calibration graph was plotted between the mean of maximum diffusion current values determined at -0.56 V (I-d) and the last nitrite concentrations (0.02-0.1 mu g/mL). The linear equation of the calibration graph was calculated by regression analysis as I-d = 445 c + 4.78 (r = 0.9997). The differential pulse polarographic method was applied for nitrite determination in five saliva samples. The Standard addition method was applied to eliminate matrix effect.
Keywords: Polarography; Nitrite; Saliva; Diffusion current; Engineering